2013
DOI: 10.1080/00405000.2012.703797
|View full text |Cite
|
Sign up to set email alerts
|

Concept of minimum electrospinning voltage (MEV) in electrospinning of PAN–DMF system: effect of distance

Abstract: Minimum electrospinning voltage (MEV), in a needle-ground plate configuration, is defined as the needle voltage at which the maximum conversion of the polymer dope into nanofibers is achieved in electrospinning. MEV is unique for a set of electrospinning parameters for a given polymer dope and the square of the MEV is directly proportional to the rate of surface formation of the nanofibers in the electrospinning process. In this study, the effect of needle to collector distance on MEV and nanofiber morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Early drying of the polymer jet may be the reason for the increase in average diameter and bead formation at a distance of 20 cm. At the same time the distance tends to change the areal density due to the variation of the spread of fibers [26]. Figure 8 is given for the comparison of variation of Water contact angles are useful for the determination of wettability of polymer materials.…”
Section: Variation In Needle Tip-collector Distancementioning
confidence: 99%
See 1 more Smart Citation
“…Early drying of the polymer jet may be the reason for the increase in average diameter and bead formation at a distance of 20 cm. At the same time the distance tends to change the areal density due to the variation of the spread of fibers [26]. Figure 8 is given for the comparison of variation of Water contact angles are useful for the determination of wettability of polymer materials.…”
Section: Variation In Needle Tip-collector Distancementioning
confidence: 99%
“…There are various reports on the deviation of the average diameter of the electrospun fibers by the variation of the applied electric current. The minimum electron volt required for the deposition of ultrafine fibers during electrospinning is directly related to the needle tip-collection plate distance [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…MEV was determined as per the reported method. 5 The electrospinning was carried out using an infusion syringe pump (KDS 100 from KD Scientic, Massachusetts USA) with a at tip needle (inner diameter of 0.84 mm) as the spinning head and 40 kV high voltage supply (DES 40 PN from Gamma high voltage, Florida, USA). The distance from the tip of the needle to the collector was kept as 15 cm and a ow rate of 0.25 ml h À1 was used.…”
Section: Electrospinningmentioning
confidence: 99%
“…The electrospinning of control PVA (14% w/w) was smooth and continuous. Our group has recently reported the inuence of polymer elasticity and other electrospinning parameters such as spinning distance and ow rate on morphology of nanobres based on PAN/DMF 3,5,26,27 and PVA/water systems. 4 It was found that when PVA was electrospun at MEV, the diameter of the nanobres did not change signicantly with either the spinning distance or the ow rate.…”
Section: Electrospinning Of Composite Nanobres Loaded With Ps/od Nan...mentioning
confidence: 99%
See 1 more Smart Citation